Powojenni lokatorzy budynku przy ul. Tłomackie 5 - Haska, Agnieszka; Bańkowska, Aleksandra (Zagłada Żydów. Studia i Materiały, 2012)
In 1945 the building of the Central Judaist Library was inhabited by ca. 30 illegal tenants. After the real estate had been taken over in February 1946 by the Central Commission of Polish Jews most of them moved, but one family refused to leave the apartment they had been living in. Certain files that have survived in the Legal Department of the Archive of the Jewish Historical Institute contain correspondence regarding the rooms on Tłomackie Street, which allow for a reconstruction of the dispute that began in 1948 and which this article describes. Aside from the profiles of the illegal tenants we also present the profiles of the legal tenants of the building at Tłomackie Street No. 5